Unformatted text preview: e. y = (x − 3)2 − 9 + 7 • Simplify the constant terms. y = (x − 3)2 − 2 Answer: +7 y = (x − 3)2 − 2 is the vertex form of the given quadratic function. example: Rewrite y = −2x2 − 4x + 1 in vertex form by completing the square.
• Get the equation ready to complete the square.
Factor −2 from the first two terms. y = −2[x2 + 2x +1 • Complete the square in the parenthesis; also
subtract that amount in the parenthesis. y = −2[x2 + 2x + 1 − 1] + 1 • Write the perfect square trinomial as a square. y = −2[(x + 1)2 − 1] + 1 • Distribute the −2 to the square and −1. y = −2(x + 1)2 −2(−1) + 1 • Simplify the constant terms. y = −2(x + 1)2 + 3 Answer: y = −2(x + 1)2 + 3 is the vertex form of the given quadratic function. exercise: Rewrite y = 20x − 5x2 in vertex form by completing the square. [Answer: y = −5(x − 2) + 20] exercise: Rewrite y = 3x2 − 2x − 1 in vertex form by completing the square. [Answer: y = 3(x − 2 1 )2 − 4
3
3 exerci...
View
Full
Document
This document was uploaded on 02/16/2014 for the course MATH PreCalcul at Holy Cross Regional High School.
 Fall '11
 Aytona
 Calculus, PreCalculus, Polynomials

Click to edit the document details